2016
DOI: 10.1155/2016/3054578
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Underlying Genetics of Craniofacial Morphology through Various Sources of Knowledge

Abstract: The craniofacial complex is the billboard of sorts containing information about sex, health, ancestry, kinship, genes, and environment. A thorough knowledge of the genes underlying craniofacial morphology is fundamental to understanding craniofacial biology and evolution. These genes can also provide an important foundation for practical efforts like predicting faces from DNA and phenotype-based facial diagnostics. In this work, we focus on the various sources of knowledge regarding the genes that affect patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 74 publications
1
35
0
2
Order By: Relevance
“…Around 40% of the variance in AHI has been shown to be explained by genetic factors . Twin and family studies suggest that ventilatory responsiveness to either hypoxemia or hypercapnia, obesity and craniofacial morphology are also under a high degree of genetic control, with 30–70% of phenotypic variance being explained by shared familial factors . The genetic basis of sleep duration and quality is poorly defined.…”
Section: The Genetic Epidemiology Of Osa and Associated Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 40% of the variance in AHI has been shown to be explained by genetic factors . Twin and family studies suggest that ventilatory responsiveness to either hypoxemia or hypercapnia, obesity and craniofacial morphology are also under a high degree of genetic control, with 30–70% of phenotypic variance being explained by shared familial factors . The genetic basis of sleep duration and quality is poorly defined.…”
Section: The Genetic Epidemiology Of Osa and Associated Traitsmentioning
confidence: 99%
“…28 Twin and family studies suggest that ventilatory responsiveness to either hypoxemia or hypercapnia, obesity and craniofacial morphology are also under a high degree of genetic control, with 30-70% of phenotypic variance being explained by shared familial factors. [30][31][32][33] The genetic basis of sleep duration and quality is poorly defined. Heritability has been estimated at~40% for measures of sleep duration, 34 25-45% for insomnia 35 and 17% for excessive daytime sleepiness, 35 but few genetic factors are known.…”
Section: Analytic Approaches To Detect Genes For Complex Diseases Sucmentioning
confidence: 99%
“…However, our knowledge of which genetic variants are responsible for human facial variation is still lacking 1 . Several genome-wide association studies (GWAS) have each identified a handful of loci associated with a small number of facial traits, few of which have been replicated 27 .…”
mentioning
confidence: 99%
“…Given the genetic variability across these conditions, it can be difficult to obtain definitive genetic diagnoses. To combat these difficulties, studies have suggested the use of phenomic databases to help identify functional groups of genes (Birgfeld et al, 2011;Rahman & Rahman, 2019;Roosenboom, Hens, Mattern, Shriver, & Claes, 2016). Rahman and Rahman (2019) noted the benefits of gene-to-phenotype databases and niche expert phenomic resources to assist in clinical diagnosis and/or clinical management.…”
Section: Introductionmentioning
confidence: 99%